1981
DOI: 10.1111/j.1476-5381.1981.tb09975.x
|View full text |Cite
|
Sign up to set email alerts
|

Insulin‐induced Enhancement of Uptake of Noradrenaline in Atrial Strips

Abstract: Addition of insulin to the organ bath increased the force of contraction of guinea‐pig left atrial strips driven electrically at 1 Hz The positive inotropic response to insulin remained unaltered in atria depleted of catecholamine or when β‐adrenoceptors were blocked by addition of propranolol to the organ bath The response of isolated atria to noradrenaline was significantly reduced in the presence of insulin Insulin affected neither the calcium accumulating abilities of the heart sarcolemma, mitochondria or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
2

Year Published

1983
1983
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 24 publications
0
25
2
Order By: Relevance
“…Furthermore, studies in vitro and in animals suggest that insulin has chronotropic and inotropic properties itself, but that this action does not dependent on changes in catecholamines (36,37). Whether the observation of an increased ability of tissues to take up NA after insulin administration bears any relation with the observed increase in the plasma clearance of NA in our study, is unclear.…”
Section: Discussioncontrasting
confidence: 48%
See 1 more Smart Citation
“…Furthermore, studies in vitro and in animals suggest that insulin has chronotropic and inotropic properties itself, but that this action does not dependent on changes in catecholamines (36,37). Whether the observation of an increased ability of tissues to take up NA after insulin administration bears any relation with the observed increase in the plasma clearance of NA in our study, is unclear.…”
Section: Discussioncontrasting
confidence: 48%
“…Several in vitro studies suggest, however, that insulin may in fact attenuate the vascular responsiveness to NA (10,35), possibly by enhancing the ability of tissue to take up NA (36). Furthermore, studies in vitro and in animals suggest that insulin has chronotropic and inotropic properties itself, but that this action does not dependent on changes in catecholamines (36,37).…”
Section: Discussionmentioning
confidence: 99%
“…Several authors have shown in animal studies and in isolated preparations that insulin increases cardiac muscle contraction, an effect which is not dependent on glucose or catecholamines [3][4][5]. Page et al [6] showed that insulin increased heart rate in diabetic patients with normal cardiovascular reflexes while Jacobsen and Christensen [7] observed that the tachycardia induced by insulin in rabbits was not inhibited by autonomic nervous blockade.…”
Section: Direct Effects Of Insulinmentioning
confidence: 99%
“…Insulin may act directly on peripheral nerve terminals. Bhagat et al [5] noted that insulin induced antagonism to NA by enhancing the ability of the tissues to take-up NA. Such a mechanism might explain the hypotensive effect of insulin in sympathectomized patients because plasma NA does not increase after insulin administration in these patients; this abnormality may result in an attenuated vasoconstrictor activity.…”
Section: Mechanisms By Which Insulin Increases Na Release and Causes mentioning
confidence: 99%
See 1 more Smart Citation